SUSTAINABILITY REPORTING, LEVERAGE, AND FIRM SIZE: IMPACT ON FINANCIAL PERFORMANCE OF ISSI MANUFACTURING FIRMS - Maulidia, Nur; Risnaeni, Umi Suswati; Hidayatullah, Indra (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Financial performance is a crucial indicator reflecting a company’s operational health and efficiency. Therefore, strong financial performance can boost investor and stakeholder confidence, supporting a company’s growth and sustainability in a competitive marketplace. The focus of this research is: 1) Does sustainability reporting significantly impact financial performance? 2) Does leverage significantly impact financial performance? 3) Does company size significantly impact financial performance? 4) Which has a greater impact on financial performance: sustainability reporting, leverage, or company size? This research employed purposive sampling with a quantitative approach. Data collection utilized secondary data and documentation. Data analysis employed multiple linear regression using IBM SPSS Statistics version 25, with a sample of 21 companies.The results of this study indicate that 1) Sustainability reporting disclosure has neither a positive nor significant effect on financial performance. This is evident from the multiple linear regression results, which obtained a significance value of 0.071 > 0.05. 2) Leverage has neither a positive nor significant effect on financial performance. This can be seen from the results of multiple linear regression which obtained a significance value of 0.323 > 0.05. 3) Company size has a positive and significant effect on financial performance. This can be seen from the multiple linear regression which obtained a significance value of 0.031 < 0.05. 4) Sustainability report disclosure, leverage, and company size simultaneously influence financial performance. This is evident from the F-test results, which obtained a significance value of 0.048 <0.05